Can Korean -(n)un mark (contrastive) focus?. (July 2016) - Kim, Ilkyu
Abstract: This paper investigates the relation between the grammar and the basic notions of information structure, focusing on Korean - (n)un and (contrastive) focus. It has been claimed that - (n)un marks contrastive focus (CF) in certain contexts. However, no consensus exists on in which context(s) it can mark CF. Moreover, the very claim that - (n)un is used to mark CF itself has been sometimes questioned and refuted. The purpose of this paper is to shed light on this issue by providing a new analysis of the relation between - (n)un and (contrastive) focus. Based on a language- and theory-independent definitions of focus, contrast, and CF, and a detailed investigation of the information structure of the relevant phenomena at issue, the main claim of this paper is that - (n)un marks relationally old information and thus cannot mark (contrastive) focus, which is necessarily relationally new by definition. How it is possible for - (n)un to mark relational givenness will be discussed based on the comparison of its inherent meaning and that of the Korean nominative marker -i/ka. Also, the standard understanding of the notion of relational givenness-newness will be critically examined in the course of unveiling the nature of the relation between - (n)un and (contrastive) focus. Highlights: Korean -(n)un is often claimed to mark contrastive focus (CF). (Contrastive) focus is relationally new by definition. Korean -(n)un cannot mark CF because it marks relationally old/given information. Its marking relationally old/given information is consistent with its inherent function of imposing salience.